1996
DOI: 10.1159/000201388
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of the Anti-Proliferative Effects of Anti-Cancer Drugs by Octreotide in vitro and in vivo

Abstract: The somatostatin analogue octreotide (SMS 201-995) exerts potent anti-proliferative effects in a number of experimental cancer models. Here we report on the inhibitory effect of octreotide in combination with the chemothera-peutic agents mitomycin C, doxorubicin, 5-fluorouracil, or taxol on the growth of AR42J pancreatic cancer cells in vitro. The dose-dependent anti-proliferative effects of mitomycin C, doxorubicin and taxol were synergistically enhanced by octreotide. Combinations of octreotide and 5-fluorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 15 publications
2
29
0
1
Order By: Relevance
“…Combinations of chemotherapy with somatostatin analogs are also receiving attention, both because of the demonstrated ability of octreotide to reduce gastrointestinal toxicity associated with certain cytotoxic agents (lOl), and because of early evidence of additive antineoplastic activity (89). Thus in experimental studies using hamsters with ductal pancreatic cancers induced by N-nitroso-bis(2-oxopropy1)amine (BOP), a 76% inhibition of tumorous pancreas weight, a significant decrease in the number of tumor nodules, an increased amount of stroma, and enhanced apoptosis were observed after therapy with somatostatin analog RC-160 plus 5-fluorouracil (5-FU) (102).…”
Section: Somatostatin Analogs As Drug Candidates Acutely and Chronicamentioning
confidence: 99%
“…Combinations of chemotherapy with somatostatin analogs are also receiving attention, both because of the demonstrated ability of octreotide to reduce gastrointestinal toxicity associated with certain cytotoxic agents (lOl), and because of early evidence of additive antineoplastic activity (89). Thus in experimental studies using hamsters with ductal pancreatic cancers induced by N-nitroso-bis(2-oxopropy1)amine (BOP), a 76% inhibition of tumorous pancreas weight, a significant decrease in the number of tumor nodules, an increased amount of stroma, and enhanced apoptosis were observed after therapy with somatostatin analog RC-160 plus 5-fluorouracil (5-FU) (102).…”
Section: Somatostatin Analogs As Drug Candidates Acutely and Chronicamentioning
confidence: 99%
“…The drugs studied include doxorubicin, paclitaxel, mitomycin C and 5-fluorouracil all of which are routinely used in the management of metastatic breast cancer (Lee et al, 1993;Weckbecker et al, 1996). The enhanced anti-tumour activity may in part be explained by the inhibitory effects of somatostatin analogues on angiogenesis, as known antiangiogenic agents such as TNP-470 and minocycline have been shown to increase the anti-tumour activity of cyclophosphamide (Patel et al, 1994;Teicher et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In this trial no additive or synergistic effect was obtained by adding chemotherapy. Therefore, the interesting observation by Weckbecker et al [29] that doxorubicin in combination with octreotide showed a significant synergistic effect in in vitro and in vivo studies remains to be proven in forthcoming randomized clinical trials.…”
Section: Combination Trial With Somatostatin Analogsmentioning
confidence: 99%
“…Thus, high dose treatment with octreotide, which only has a low binding affinity for the SSTR-3 subtype induces apoptosis both in carcinoid tumors and BON-1 cells xenotransplanted to nude mice [28]. Octreotide and other somatostatin analogs significantly inhibit the growth of the neuroendocrine-differentiated cell line BON-1, the pancreatic cancer cell line AR42J and the human breast cancer line MCF-7 in experimental animals [28,29]. Tumors treated with somatostatin analogs are less vascular than those in untreated mice suggesting that the peptide inhibits angiogenesis.…”
Section: Somatostatin Receptorsmentioning
confidence: 99%
See 1 more Smart Citation